Student Management in Developing Students' Potential through Extracurricular Activities - Agissa, Aina Warda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to explore the strategic role of student affairs management in developing students’ potential through extracurricular activities. In the context of modern education, the development of students’ academic and non-academic potential including leadership, social skills, and character building is essential. Student affairs management functions not only as an administrative system but also as a developmental strategy that facilitates student empowerment through structured programs. This research employed a qualitative approach using library research methods. Data were collected from relevant books and reputable journal articles and analyzed to understand how effective student affairs management can support student growth through extracurricular engagement. The findings indicate that well-managed extracurricular activities—based on students’ needs, interests, and contextual relevance—serve as effective platforms for holistic student development. Key components of effective management include participatory planning, systematic implementation, and continuous evaluation. Moreover, successful programs require collaboration among school leaders, teachers, extracurricular advisors, and parents. In conclusion, student affairs management plays a vital role in optimizing students’ potential both academically and personally. Through strategic and integrative approaches, extracurricular activities can significantly contribute to shaping well-rounded, disciplined, and socially responsible individuals.